Optimization and Design of Wideband Antenna Based on Q Factor - Han Liu; Chengyou Yin; Weidong Gao; Yulong Sun (International Journal of Antennas and Propagation)
A wideband antenna is designed based on Q factor in this paper. Firstly, the volume-surface integral equations (VSIEs) and self-adaptive differential evolution algorithm (DEA) are introduced as the basic theories to optimize antennas. Secondly, we study the computation of Q of arbitrary shaped structures, aiming at designing an antenna with maximum bandwidth by minimizing the Q of the antenna. This method is much more efficient for only Q values at specific frequency points that are computed, which avoids optimizing bandwidth directly. Thirdly, an integrated method combining the above method with VSIEs and self-adaptive DEA is employed to optimize the wideband antenna, extending its bandwidth from 11.5~16.5 GHz to 7~20 GHz. Lastly, the optimized antenna is fabricated and measured. The measured results are consistent with the simulated results, demonstrating the feasibility and effectiveness of the proposed method.